The Role of Problematic Types of Physics Questions in Directing the Reader to Creative Activity - Boymirov Sherzod Tuxtaevich; Gayibnazarov Rozimurod Bakhtiyorovich; Axmedova Manzura Gulomjonovna; Berdikulova Shakhsanam Umaralievna; Muminjonov Sadiqbek Ikromjonovich (Peerian Journals Publishing, 2022)
When improving the content of school education in physics using the problem type, the article describes the psychological components of a student's cognitive activity, its namelessness, the need to know, the structure of mental abilities. Using the problematic type of questions in the lesson, the features, opportunities and tasks of directing a student to creative activity are widely covered.
Keywords: problem situation; heuristics; creativity; knowledge